NEW CHALLENGES FOR TEACHER TRAINING. THE RIGHT TO PHYSICAL EDUCATION IN PERSONS WITH DISABILITIES. (Fiep Bulletin - online, 2016)
A central aspect in the design of training programs carried out in higher level institutiona is to consolidate the training of university teachers updated knowledge and practices that respond to the needs of the community. The human right to physical education is universal and should reach all people looking to improve their well-being and quality of life. This paper shows results of a research and aim is to account for the importance of physical education adapted to people with disabilities and their importance in training of future professionals.
Keywords: Teacher training - Adapted Physical Education - Human Rights